(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
The Upper Crétacé rocks of Krashok formation, Massive formation and Shiranish formation, are very important for petrol and gas reserve, where it is the importance petrol reserves in Syria. 25 samples of these two formations werestudied.The Massive formation had a good Petrological character as reserves rocks ,where it contain calc rocks, which have good reserving properties, and it cover the hole area , and it contain a petrol. Where the Shiranish formation is almost homogenies, and contain calc-marl-clay rocks with foraminifera, and it divide into three zones, depending on it is petro physical properties, the upper zone is the most absorb of petrol, by comparison whit others zones, which show there are many indicators reserve characteristicin these formation. تعد صخور الكريتاسي الأعلى لتركيب كراتشوك المتمثلة بتشكيلتي الماسيف ، والشيرانيش هامة لخزن النفط والغاز، فهي تعتبر من أهم المكامن النفطية في سورية، حيث دُرست (25 عينة) من التشكيلتين . تكون تشكيلة الماسيف ذات مواصفات بترولوجية جيدة كصخور خازنة ،ومنتجة من حيث كونها مؤلفة من صخور كلسية مسامية جيدة ومشققة ، ومنتشرة في كامل الطية ، أو تركيب كراتشوك .أما تشكيلة الشيرانيش فهي متجانسة ليتولوجياً ومؤلفة من تناوب الحجر الكلسي الغضاري والمارلي الغني بالمنخربات،حيث تم تقسيمها إلى ثلاثة نطاقات تبعاً لمواصفاتها البتروفيزيائية ، فالنطاق العلوي هو الأكثر تشرباً بالنفط من النطاقين الآخرين ، مما يدل على وجود مؤشرات من توفر المواصفات الخزنية لهذه التشكيلة.